Hukum Penggunaan Zakat Fitrah untuk Acara Halal Bihalal Perspektif Mazhab Syafi’i: Studi Kasus Kecamatan Aek Bilah, Kabupaten Tapanuli Selatan - Nursaidah Rambe; Cahaya Permata (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Zakat fitrah is an individual zakat that must be issued by Muslims who can afford it in ramadan to be allocated to those who have the right to receive it, specifically: fakir, miskin, amil, mu'allaf, riqab, gharim, fisabilillah and ibn sabil. However, in Aek Bilah District, there are cases of zakat distribution that are not on target. Zakat fitrah is used to eat together at halal bihalal events. The objective of this research is to explore the concept of distributing zakat fitrah in Aek Bilah District, the factors of using zakat fitrah to eat together at halal bihalal events, and how the law on the use of zakat fitrah for Halal Bihalal events according to the Shafi'i School. This research methodology is empirical juridical, utilizing a living case approach and conceptual approach. Data were collected by the method of interviews and document studies. Then the data is processed by qualitative methods. The results showed that in three villages in Aek Bilah District, zakat fitrah was not only distributed to the eight mustahik, but also used for halal bihalal events that had been carried out for generations, so it became a habit. The use of zakat fitrah for halal bihalal events violates the opinion of the Shafi'i School. According to the Shafi'i School, zakat fitrah can only be distributed to eight groups called Allah in Q.S At-Tawbah, verse 60. While eating together at halal bihalal events is not part of mustahik zakat.